How fibrosis influences imaging and surgical decisions in pancreatic cancer - Erkan, Mert; Hausmann, Simone; Michalski, Christoph W.; Schlitter, Melissa; Fingerle, Alexander A.; Dobritz, Martin; Friess, Helmut; Kleeff, Jörg (Frontiers in Physiology, 2012)
Our understanding of pancreatic ductal adenocarcinoma is shifting away from a disease of malignant ductal cells-only, towards a complex system where tumor evolution is a result of interaction of cancer cells with their microenvironment. This change has led to intensification of research focusing on the fibrotic stroma of pancreatic ductal adenocarcinoma. Pancreatic stellate cells are the main fibroblastic cells of the pancreas which are responsible for producing the desmoplasia in chronic pancreatitis and pancreatic ductal adenocarcinoma. Clinically, the effect of desmoplasia is two-sided; on the negative side it is a hurdle in the diagnosis of pancreatic ductal adenocarcinoma because the fibrosis in cancer resembles that of chronic pancreatitis. It is also believed that pancreatic stellate cells and pancreatic fibrosis are partially responsible for the therapy resistance in pancreatic cancer. On the positive side, a fibrotic pancreas is safer to operate on compared to a fatty and soft pancreas which is prone for postoperative pancreatic fistula. In this review the impact of pancreatic fibrosis on diagnosis of pancreatic cancer and surgical decisions are discussed from a clinical point of view.